Balancing the formal and the informal in user-centred design - Harrison, Michael D. (2021)
This paper explores the role of formal methods as part of the user-centred design of interactive systems. An iterative process is described, developing prototypes incrementally, proving user-centred requirements while at the same time evaluating the prototypes that are executable forms of the developed models using ‘traditional’ techniques for user evaluation. A formal analysis complements user evaluations. This approach enriches user-centred design that typically focuses understanding on context and producing sketch designs. These sketches are often non-functional (e.g. paper) prototypes. They provide a means of exploring candidate design possibilities using techniques such as cooperative evaluation. This paper describes a further step in the process using formal analysis techniques. The use of formal methods provides a systematic approach to checking plausibility and consistency during early design stages, while at the same time enabling the generation of executable prototypes. The technique is illustrated through an example based on a pill dispenser.